Pengaruh Lingkungan Sekolah Terhadap Motivasi Belajar Siswa Pada Mata Pelajaran Pendidikan Agama Islam Di SMAN 3 Pekanbaru - Miftha Hulladuni Riandi (Al-Abshor : Jurnal Pendidikan Agama Islam, 2026)
This study aims to determine the influence of the school environment on students' learning motivation in Islamic Religious Education subjects at SMAN 3 Pekanbaru. The study used a quantitative approach with a correlational method. The sample in this study was 43 grade X students who were selected proportionally from a population of 430 students. Data collection techniques were carried out through questionnaires and documentation. The results of the study showed that the school environment consisting of physical, social, and academic aspects had a significant influence on students' learning motivation. A conducive environment has been proven to be able to increase students' learning motivation, as indicated by indicators of student activity, enthusiasm for learning, and participation in learning activities. This happens because the school environment creates a comfortable atmosphere, positive social interactions, and adequate facilities. The conclusion of this study is that the school environment has a positive effect on students' learning motivation, especially in the context of Islamic Religious Education learning. This finding has an impact on the importance of effective school environment management as a strategy to improve the quality of learning. Abstrak Penelitian ini bertujuan untuk mengetahui pengaruh lingkungan sekolah terhadap motivasi belajar siswa pada mata pelajaran Pendidikan Agama Islam di SMAN 3 Pekanbaru. Penelitian menggunakan pendekatan kuantitatif dengan metode korelasional. Sampel dalam penelitian ini adalah 43 siswa kelas X yang dipilih secara proporsional dari populasi sebanyak 430 siswa. Teknik pengumpulan data dilakukan melalui angket dan dokumentasi. Hasil penelitian menunjukkan bahwa lingkungan sekolah yang terdiri dari aspek fisik, sosial, dan akademis memiliki pengaruh yang signifikan terhadap motivasi belajar siswa. Lingkungan yang kondusif terbukti mampu meningkatkan dorongan belajar siswa, ditunjukkan melalui indikator keaktifan siswa, semangat belajar, dan partisipasi dalam kegiatan pembelajaran. Hal ini terjadi karena lingkungan sekolah menciptakan suasana yang nyaman, interaksi sosial yang positif, serta fasilitas yang memadai. Kesimpulan dari penelitian ini adalah bahwa lingkungan sekolah berpengaruh secara positif terhadap motivasi belajar siswa, khususnya dalam konteks pembelajaran Pendidikan Agama Islam. Temuan ini berdampak pada pentingnya pengelolaan lingkungan sekolah yang efektif sebagai strategi peningkatan kualitas pembelajaran